TOLERANSI UMAT ISLAM DAN HINDU ( STUDI KASUS DI DESA BALONGGARUT KECAMATAN KREMBUNG KABUPATEN SIDOARJO ) - DIANTINA, RIA; Warsono (Universitas Negeri Surabaya (Unesa), 2024)
This research aims to describe the tolerance of the people of Balonggarut Village, Krembung District, Sidoarjo Regency as well as encouragement and hope for religious differences. The targets of this research were Muslim and Hindu communities in Balonggarut Village. The theory used in this research is the Phenoenological Theory developed by Alfred Shut. The approach used in this research is a case study with qualitative methods. This research took informants from the head of Balonggarut Village, Hindu religious leaders, and Muslim communities as research subjects. The data collection techniques used were observation, in-depth interviews and documentation. The results of the research show that tolerance in Balonggarut Village, Krembung District, Sidoarjo Regency is at a good level. Through forms of tolerance such as mutual respect, respect and affection for differences with the form of mutual cooperation that is created by participating in the Nyepi holiday and social service. As well as encouragement to be tolerant of religious differences by avoiding disputes and the hope of creating peace in Balonggarut Village, Krembung District, Sidoarjo Regency.